Gut microbiota of captive common bottlenose dolphins Tursiops truncatus gilli: influence of age, sex, birthplace, and contacts with dolphinarium visitors - Popov, Igor V.; Suvorova, Irina V.; Krikunova, Anastasya A.; Chebotareva, Iuliia P.; Tikhmeneva, Iuliia A.; Venema, Koen; Ermakov, Alexey M. (Frontiers in Marine Science, 2024)
Dolphins are aquatic mammals, whose role in microbial ecology is not fully understood. It is critical to study the microbiota of dolphins kept in captivity, as close contact with humans could unpredictably affect both human and animal health. In this study, we investigated the gut microbiota of 15 captive common bottlenose dolphins, and the relationship of microbial diversity and composition with animals’ age, sex, birthplace (dolphinarium or wildlife), and direct contacts with dolphinarium visitors using high-throughput V3-V4 16S rRNA amplicon sequencing. Based on acquired sequencing data we calculated and compared alpha and beta diversity indexes, as well as conducted differential abundance analysis of identified bacterial taxa to find multivariable associations with dolphins’ age period, sex, birthplace, and type of contact with humans with linear models. There was no association between gut microbiota composition and diversity and dolphins’ age period, sex, and birthplace. However, there were significant differences (q-value≤0.00018) in the relative abundance of Edwardsiella genus in dolphins that were in contact only with dolphinarium staff in comparison to dolphins that apart from dolphinarium staff also had contact with dolphinarium visitors. These results show that dolphins born in wildlife and dolphinariums do not have significant differences in gut microbiota composition and the microbiota of captive dolphins can be affected by their contact with humans.